O herói desmascarado: a imagem do masculino nos editoriais da revista inglesa "Arena Homme Plus" entre 1995 e 2007 - Queiroz, Mário Antônio Pinto de (2008)
The objective of this study is to analyze how fashion editorials reflect the image of man at the turn of the 21st century, and discuss the relation between fashion and the hero in the masculine world. It aims at discussing whether man s fashion through the images developed for this magazine points at transformations in the behavior of men or maintains conservative traits that restrict novelties in men s outfits and behavior. The magazine chosen Arena Homme Plus is one of the few magazines worldwide that is exclusively geared towards men s fashion. This British publication features major designers from Europe and the United States and circulates worldwide showing the work of designers, photographers, producers thus influencing the fashion industry and consumers. This study starts by focusing on the early days of fashion photography in the 1920s when photographs begin to replace illustration. It points out that a journalistic production geared to the male public had been around since the 19th century and included from men s magazines with essays of female nudes to our object of study: men s fashion magazines. The study focuses on the photo essays, the fashion editorials, of these issues published in the late 1990s and beginning of the third millennium and on the content revealed through the eyes of major contemporary photographs and though the choices made by fashion professionals during the production stage. Fashion editorials account for most of the content of Arena Homme Plus and each issue may include up to six of them, with an average of forty photographs. The editorials were chosen according to their relevance to discuss the hero, investigating the different faces of man at the turn of the millennium. The theoretical framework includes the concepts of imprinting, imaginary and noosphere as developed by Edgard Morin. The analysis is based on the theoretical framework provided by semiotics as applied to the field of culture, specifically to fashion. The study concludes that the image of man has been shattered into myriad variations so that it is no longer possible to try to think of the masculine as a single segment, something that vanguard fashion magazines, such as Arena Homme Plus, have long recognized